Performance of upland rice strains in reaction to fungal diseases - Alves, Natália Botega; Castro, Douglas Goulart; Félix, Marco Renan; Tomé, Laís Moretti; Neto, Antônio Rosário; Botelho, Flávia Barbosa Silva (Scientia Agraria Paranaensis, 2021)
The control of the impact of diseases on plants can be carried out via breeding, through the development of cultivars less susceptible to pathogens. Therefore, this study aimed to assess the severity of fungal diseases in upland rice strains from the Cultivation and Use Value test, belonging to the Upland Rice Breeding Program” of Federal University of Lavras (UFLA), in partnership with “EMBRAPA Rice and Beans” and the “Minas Gerais Agricultural Research Company” (EPAMIG). The experiment was installed in the municipalities of Lambari and Lavras, both in Minas Gerais, Brasil, in the 2015/2016 and 2016/2017 seasons, in a randomized block design with three replications. Were evaluated 14 lines, 11 lines of the program and 3 commercial witnesses, regarding the intensity of diseases (leaf and neck blast, brown spot, grain spot and scalding). There was a significant difference between lineages for all traits, except brown spot, indicating the presence of genetic variability for the characters in question. The study of the interaction was performed, decomposing the statistically significant ones in simple and complex interactions. The experiment presented a coefficient of variation from 29% to 56% and accuracy from 56% to 95.5%, indicating that the estimates were obtained with good to medium experimental precision. It is essential to evaluate diseases in breeding programs in order to select cultivars that are increasingly resistant, as these affect not only productivity, but the quality and final yield of grains. The genotypes CMG 2119 (5), CMG 2162 (1), CMG 1896 (13) and CMG 2168 (2) were shown to be more tolerant to all diseases simultaneously, being, therefore, the most suitable for the launch, considering the character disease resistance. The Upland Rice Breeding Program of UFLA has lines with variability for resistance, strains with potential for release.